Analysis of Syntactic Errors in Writing of Third Semester Students of the Department of English and Literature - H, A Nurmilatul; Saitakham, Kiattichai (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research presents the results of research on syntactic errors in writing produced by third semester students of the Department of English and Literature, Alauddin State Islamic University, Makassar. The aim of this research is to identify the dominant types of syntactic errors and provide in-depth insight into the error patterns that frequently occur. Methodology: The research method used is descriptive qualitative by collecting data from students' final written exam sheets. Data collection involved obtaining final writing exam sheets from third semester AG 1&2 students enrolled in the Department of English and Literature at Alauddin State Islamic University Makassar. Main Findings:The analysis results show that the most common syntax errors include omissions, additions, information errors, and ordering errors. Novelty/Originality of this study:The novelty of this research lies in the focus of analyzing syntactic errors during the third semester students studying English and Literature. with a more comprehensive and detailed approach than previous research.